Mechanical characterization of plastic soil treated with eggshell lime additive. - Ibrahim J. Al Sinjary; Dr. Saleh J. Suleiman; Dr. Harith E. Ali (Genius Journals, 2022)
Egg shells are one of the materials rich in calcium carbonate (caco3), and they are wastes that are thrown in large quantities(Consoli et al., 2019). Therefore, reusing these wastes in engineering works is one of the objectives of this study. The eggshell powder lime (ESL) was selected and 6% from the dry soil weight was selected as the optimum ratio. It was used to improve the mechanical properties of medium to high plasticity of the soil with a moisture content of 20%. The results showed a significant improvement in the strength of unconfined compressive strength, as well as the improvement of the direct shear and the improvement of the flexural strength of the samples. The results showed also an improvement in the compressive strength of the curing time of soil for periods of 7,14,28,50,100 days
Keywords: Eggshells; Eggshell’s lime powder; Plastic soils; Soil treated with Lime